When You're Out, You're Not Really Out: Exiting Strategies Among Gang-Affiliated Chicanas - Abigail F. Kolb; Ted Palys; Ashley Green (Journal of Public and Professional Sociology, 2019)
In recent years there has been an increased focus on gang desistence and exiting strategies, yet little is known at present regarding the experiences of women exiting the gang lifestyle. The current study, based on semi-structured interviews with twenty-four formerly gang-affiliated Chicana women involved with a prominent gang prevention/intervention organization, sought to understand how these women negotiated their disengagement from the gang. Consistent with previous literature, we found that disengagement from the gang lifestyle is neither linear nor immediate. Five primary themes that emerged from the interviews included: (1) the process of identity transition; (2) motherhood and its responsibilities; (3) generational shifts in gang culture; (4) burning bridges; (5) impacts of prison; and (6) support services. The women's narratives offer an alternative lens through which to understand women’s negotiation of their own identities through the process of disengagement from the gang.